Zinc Coordination Polymers Containing Isomeric Forms of p-(Thiazolyl)benzoic Acid: Blue-Emitting Materials with a Solvatochromic Response to Water - Staderini, Samuele; Tuci, Giulia; Luconi, Lapo; Mueller, Philipp; Kaskel, Stefan; Eychmueller, Alexander; Eichler, Franziska; Giambastiani, Giuliano; Rossin, Andrea (European Journal of Inorganic Chemistry, 2017)
Two coordination polymers of assorted dimensionality (1D, 2D) have been prepared, namely [Zn3(L2Th)4(OH)2·2(HL2Th)]∞ (1) and [Zn(L5Th)(OAc)]∞ (2), starting from ZnII salts and the isomeric forms of the organic linker p-(thiazolyl)benzoic acid: p-(2-thiazolyl)benzoic acid (HL2Th) and p-(5-thiazolyl)benzoic acid (HL5Th). The isomers have been prepared ad hoc, following straightforward Pd-catalyzed C–C coupling reaction protocols. In 1, the deprotonated ligand is coordinated through its carboxylate group only, with dangling thiazole groups. The –COO– units are bridging adjacent metal centers, thus creating a 1D chain. The Zn3 cluster is made of one six-coordinate (Oh) and two four-coordinate (Td) ZnII ions; triple-bridging µ3-OH groups are balancing the overall positive charge. The structure of 2 is instead made of Zn2(carboxylate)4 “paddle-wheel” dimers as the constituting inorganic node. The octahedral metal coordination sphere includes two µ-(κ-COO) benzoate spacers, two µ-(κ-COO) acetate ions, the thiazole N atoms coming from adjacent building blocks, and a weak Zn···Zn axial interaction. The resulting final assembly is two-dimensional (2D), where p-(5-thiazolyl)benzoate adopts a genuine µ-[κ(COO):κ(N)] bridging coordination mode. The luminescent properties of both polymers have been analyzed in the solid state; they feature ligand-centered emissions at λ = 434 nm (1) and λ = 427 nm (2). These electronic transitions fall in the visible region, giving the samples a characteristic blue color under an ordinary UV lamp (excitation at λ = 254 nm). The theoretical analysis of the electronic features of the ligands and related molecular orbitals reveals that the observed transitions are mainly of π→π* nature, involving π orbitals delocalized on both aromatic cycles. A significant (reversible) blueshift of the emission maximum of ca. 60 nm, from the visible to the UV region, has been observed for 1 when suspended in water.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Coordination polymers; Luminescence; Solvatochromism; Thiazole; Zinc